Adsorption of Methylene Blue from an Aqueous Solution using Epichlorohydrin Modified of Rubber Seed Kernel - Alexandria, Tiffany
One of major problems of industrial wastes, which using dye, is the dyeing effluent. Methylene blue (MB) is a dye which is difficult to be degraded naturally because of its heterocyclic aromatic structure. Many treatment methods have been developed, however the cost of its operation is high. Therefore, developing a cheap MB treatment method is urgently required. This study aims to investigate the use of Rubber (Hevea brasiliensis) Seed which was modified by epicholorhydrin and chemicaly activated with concentrated sulphuric acid as a novel adsorbent to adsorb MB from an aqueous solution in batch mode. Synthesis of the adsorbent was done by varying impregnation ratio and duration of rubber seed with epichlorohydrin and concentrated sulphuric acid. Characterizations of the rubber seed before modification, after modification, and after activation were done with Fourier Transform Infrared (FTIR) and Scanning Electron Microscope (SEM). Modified activated rubber seed was tested with fuction of pH, initial concentration, contact time, and amount of adsorbent. In addition, the influence of the existence of cationic intruder, which was Neutral Red, to the adsorption capacity of MB by active epicholorohydrin modified rubber seed adsorbent, was investigated. Two models of adsorption isotherm, which are Langmuir and Freundlich isotherm, were investigated to describe the term when the adsorption proccess reach the equilibrium state. Kinetic models used to interpret adsorption data were pseudo-first-order and pseudo-secondorder models. The results of experiment showed that optimum modification occurred at impregnation ratio of rubbber seed and epichlorohydrin of 1:6 (w/w) in 2 hours, whereas optimum activation occurred at impregnation ratio of rubbber seed and concentrated sulphuric acid of 1:6 (w/w) in 5 hours. The result of MB adsorption by modified-activated rubber seed testing showed that optimum adsorption was reached at pH 12; MB concentration of 800 ppm, equilibrium state was reached at 90 minutes of contact time, and with 0.01 g adsorbents. The results of the kinetic study showed that the adsorption of MB by the adsorbent could be described by pseudo-second-order kinetic model. Thermodynamic parameter data indicated that adsorption process of the adosrbent was not spontaneous with the Gibbs free energy (?G) values are 0.779 kJ/mol at 25 °C and descreased to -1.324 kJ/mol at 45 °C and -3.427 kJ/mol at 65 °C. Adsorption process occurred endotermically with enthalpy (?H) value of 32.118 kJ/mol. In accordance to the results, the value of entropy (?S) obtained was 105.164 J/mol with activation energy (Ea) of 32.634 kJ/mol.